MANAJEMEN LABA DENGAN CLASSIFICATION SHIFTING: PENGUJIAN LABA USAHA DAN POS LUAR BIASA (STUDI EMPIRIS DI NEGARA-NEGARA ASEAN) - Wulandari, Soliyah; Kusuma, Indra Wijaya (UI Scholars Hub, 2013)
Earnings management using classification shifting is interesting because many previous researches have shown that analyst and investors pay more attention to core earnings (investors give low weight on transitory earnings). Extraordinary items are transitory items or irregular items and their allocation require management subjectivity, thus allowing management to exercise classification shifting using extraordinary items to increase core earnings. This research aims to detect earnings management through classification shifting by classifying core expenses as extraordinary items to increase core earnings. Samples of this research obtained with purposive sampling from all companies listed in the capital markets of Indonesia, Malaysia, Singapore, Philippines, Thailand, and Vietnam. Final samples are 126 observations from 2004 until 2008. Data analysis was performed using multiple regressions. Results show that extraordinary items current year are positively associated with unexpected core earnings this year, but extraordinary items this year are also positively associated with unexpected change in core earnings in the following year. This research does not provide empirical support for classification shifting by companies listed in the capital markets of Indonesia, Malaysia, Singapore, Philippines, Thailand, and Vietnam. An unexpected increase in core earnings is more consistent with real economic improvements.